The difference in clinical knowledge between staff employed at faith-based and public facilities in Malawi - Wiktoria Tafesse; Martin Chalkley (Health for All Nations, 2024)
Empirical evidence concerning differences in the quality of service offered by faith-based and public healthcare facilities in low-and middle-income countries is limited. This study contributes by examining the difference in clinical knowledge of staff based at faith-based and government facilities in Malawi. Using vignette data for individual healthcare workers from the 2018/2019 Malawi Harmonised Health Facility Assessment, we performed regression analysis of the relationship between ownership and the probability of respondents making the correct diagnosis, treatment, and management choices for eight childhood, adult, and pregnancy-related cases accounting for differences across healthcare workers, facilities, and geography. Staff employed at faith-based facilities, compared to staff at public facilities, are found less likely to correctly diagnose and treat children presenting with diarrhoea with severe dehydration but are better at diagnosing and treating adults presenting with diabetes. We do not find any differences in the diagnosis and treatment of the remaining six cases. Hence, we do not find compelling evidence of an overall difference in clinical knowledge across staff at faith-based compared to public facilities in Malawi.